Association between relative grip strength and depression among U.S. middle-aged and older adults: results from the NHANES database - Sun, Aochuan; Liu, Zhengtang (Frontiers in Public Health, 2024)
Background: Mental health issues among middle-aged and older adults are gaining increasing attention. Recent studies have shown that relative grip strength is associated with cardiovascular diseases and various cancers, but its relationship with depression remains unclear.This cross-sectional study included data from adults aged 50 years and older from the 2011-2014 National Health and Nutrition Examination Survey. Relative grip strength is calculated by dividing the maximum absolute grip strength of both hands by BMI. The Patient Health Questionnaire (PHQ-9) was used to evaluate the depressive outcome. Multivariate logistic regression was performed to assess the association between relative grip strength and depression.Results: In this study, a total of 3,639 participants (≥50 years) with a mean age of 64.3 ± 9.3 years were enrolled, of whom 48.9% were male. Compared with individuals with lower relative handgrip strength in Q1 (≤1.64 kg/BMI), the adjusted OR values for relative handgrip strength and depression in Q2 (1.64-2.17 kg/BMI), Q3 (2.17-2.84 kg/BMI), and Q4 (≥2.84 kg/BMI) were 0.69 (95% CI: 0.51, 0.93, P =0.016), 0.36 (95% CI: 0.24, 0.55, P <0.001), and 0.32 (95% CI: 0.20, 0.51, P <0.001), respectively. T he relationship between relative grip strength and depression presented an L-shaped curve (nonlinear, P =0.006), with an inflection point of roughly 2.98 kg/BMI. Among participants with relative grip strength < 2.98 kg/BMI, the OR of incident depression was 0.41 (95% CI: 0.30-0.55, P <0.001) Conclusions: Our findings indicated that relative grip strength was inversely associated with incident depression and demonstrated an L-shaped relationship among U.S. middle-aged and older adults. Relative grip strength could be the indicator for future screening of mental health.